2014
DOI: 10.3409/fb62_3.163
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Breeding Region and Season on the Content of Some Trace Elements and Heavy Metals in the Hair of Cows

Abstract: breeding region and season on the content of some trace elements and heavy metals in the hair of cows. Folia Biologica (Kraków) 62: 163-169. The aim of the research was to determine the effect of the season and the breeding region on the content of selected minerals (Zn, Cu, Mn, Fe, Pb, Cd) in the hair of dairy cows. The research material covered 114 Holstein-Friesian breed cows from three breeding centres in Poland, hereafter referred to as A, B and C. Breeding centre A is located in Opolskie province, breedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 12 publications
2
12
5
1
Order By: Relevance
“…In this case, the largest share in these relationships is ascribed to the hair and liver, as well as to the hair and kidneys. This may indicate that the hair is a good matrix for the initial assessment of animal exposure to various metals, which was confirmed, among others, by Cygan-Szczegielniak et al [ 5 , 13 ] and other authors [ 3 , 14 ]. Moreover, the hair may be collected from the animal in vivo, which in some cases is of great importance.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In this case, the largest share in these relationships is ascribed to the hair and liver, as well as to the hair and kidneys. This may indicate that the hair is a good matrix for the initial assessment of animal exposure to various metals, which was confirmed, among others, by Cygan-Szczegielniak et al [ 5 , 13 ] and other authors [ 3 , 14 ]. Moreover, the hair may be collected from the animal in vivo, which in some cases is of great importance.…”
Section: Discussionsupporting
confidence: 60%
“…The exception was the hair of red deer, in which Cd concentration was 50% lower (0.13 mg·kg −1 of d.w.) than in muscles of fallow deer. Animal hair is certainly one of the most important matrices that can be used as a bioindicator of trace elements in the environment [ 5 , 13 ], as with human hair [ 14 ]. The content of individual macro- and microelements as well as Pb and Cd in the hair of red deer was comparable to the content measured in the same matrix from red deer in the season before the present study [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Present content of Cd was higher than critical limit of Cd in blood of animals 0.5 mg/L as observed by WHO (2000). (Krupa et al, 2006: Cygan-Szczegielniak et al, 2014: Gabryszuk et al,2008:Su et al, 2017 (2010) noted values ranged from 0.02 to 0.08mg/L both of the ndings were Found lower than current observed concentration of Cd in irrigation water while safe limit of Cd in water was reported 0.01mg/L (Pescod ,1992) our concentration of Cd surpass this concentration. Alrawiq et al(2014) reported BCF values varied from 0.221-0.490 mg/kg lower than present study.…”
Section: Discussionmentioning
confidence: 54%
“…Hair analysis has been studied in various animal species: livestock (Combs 1987;Christodoulopoulos et al 2003;Cygan-Szczegielniak et al 2014), sheep (Hawkins and Ragnarsdottir 2009), goats Pitropovska et al 2014 SD -standard deviation, C -colour; * Significance P ≤ 0.05, *** Significance P ≤ 0.001, ns -not significant , camels (Faye and Seboussi 2009), mule deer (Roug et al 2015), horse (Dunnett and Lees 2003;Asano et al 2005) and seals (Ikemoto et al 2004). Some of these studies show the diagnostic potential of hair analysis.…”
Section: Discussionmentioning
confidence: 99%